Modified-ZrO₂ Supported Bimetallic Ruthenium-Tin Catalysts for Selective Hydrogenolysis of Furfuryl Alcohol to 1,5-Pentanediol - Ikhsan Mustari; Anggita Nurfitriani; Arif Ridhoni; Firza Almervanka; Utami Irawati; Thea Seventina Desiani Bodoi; Atina Sabila Azzahra; Rodiansono Rodiansono (Chemistry Department, Faculty of Sciences and Mathematics, Diponegoro University, 2026)
Biomass-derived platform C5-furanic compounds such as furfural (FFald) and furfuryl alcohol (FFalc) can be converted into 1,5-pentanediol (1,5-PeD), an important intermediate for textiles and plastics, via catalytic hydrogenolysis reaction. However, catalyst selectivity for the hydrogenolysis reaction of FFalc to 1,5-PeD remains a challenge. In this study, modification of ZrO2 with metal oxides such as TiO2(R), TiO2(A), g-Al2O3, and active carbon (C) as the supports of bimetallic ruthenium-tin (Ru-Sn) catalysts for the selective hydrogenolysis of furfuryl alcohol (FFalc) to 1,5-pentanediol (1,5-PeD) has been investigated systematically. The modified-ZrO2 supports were prepared by physical mixing using oxalic acid as a binder at room temperature, followed by calcination under N2 at 300°C (ramping 2.5°C min−1) for 2 h. The supported Ru-Sn catalysts were synthesised by using the coprecipitation-hydrothermal method at 150°C for 24 h and reduced with H2 at 400°C (ramping 3.3°C min−1) for 2 h. The synthesised catalysts were characterised by means of XRD, H2-TPR, and NH3-TPD. The pristine structures of ZrO2, TiO2, and g-Al2O3 were maintained during the preparation of catalysts. Ru-Sn/ZrO2-TiO2(A) catalyst (Ru = 4 wt%, Sn = 1.30 wt%, ZrO2 = 67 wt%, and TiO2 (A) = 33 wt%) with calcination temperature of 300°C gave the highest yield of 1,5-PeD (72%) at 140°C, H2 10 bar for 3 h.